The Influence of Communication Studies on the Culture of Life in Cemara Jaya Karawang Village - Sri Wahyuni; Djone Georges Nicolas; Adolf Bastian Butarbutar; Vroly Rut Wowor; Leyna Nainggolan (Jurnal Pengabdian Masyarakat Bestari, 2022)
The aim of the research is to study the influence of communication science on the culture of life. The role of cultural life is something that is important in the economic growth and development of society in a region, and the science of communication also has a role in participating in enhancing the cultural development of people's life in a region. Research population 34 people with a research sample of 30 people. The method used is a quantitative research method with data analysis tests carried out with a crude product moment correlation test or Pearson correlation. This research consists of 2 (two) variables, namely Communication Science (X) as the independent variable and Life Culture (Y) as the dependent variable. With the problem under study: The Effect of Communication Studies on the culture of life in Cemara Jaya Village, Cibuaya District, West Karawang Regency. The results of the study show that there is a significant and strong relationship between the science of communication and the culture of life. This is evidenced by the correlation value or influence value of 0.883, the value of α = 0.000. The science of communication has an influence on the culture of life (X → Y), the science of communication has a role in helping to enhance the development of the culture of people's life in a region and the culture of life has a role and is important in the economic growth and development of people in a region.